Klf5 acetylation regulates luminal differentiation of basal progenitors in prostate development and regeneration - Baotong Zhang (Nature Portfolio, 2020)
The role of the Klf5 in early and postnatal prostate development and in regeneration is unclear. Here, the authors show that Klf5 acetylation regulates and maintains luminal differentiation of prostate basal progenitors and is essential following androgen-induced regeneration.